Impact of the improvement of living conditions on tuberculosis mortality in Brazil: an ecological study - Natividade, Marcio; Pereira, Marcos; Stauber, Christine; Miranda, Samilly; Teixeira, Maria Glória; Souza, Ramon Andrade de; Anjos, Marilia Santos dos; Barros, Rafael; Morato, Daniela Gonçalves; Aragão, Erika; Pereira, Susan Martins; Costa, Maria da Conceição Nascimento (São Paulo Medical Journal, 2025)
BACKGROUND: The risk of death due to tuberculosis (TB) in Brazil is high and strongly related to living conditions (LC). However, epidemiological studies investigating changes in LC and their impact on TB are lacking. OBJECTIVES: To evaluate the impact of LC on TB mortality in Brazil. DESIGN AND SETTING: This ecological study, using panel data on spatial and temporal aggregates, was conducted in 1,614 municipalities between 2002 and 2015. METHODS: Data were collected from the Mortality Information System and the Brazilian Institute of Geography and Statistics. The proxy variable used for LC was the Urban Health Index (UHI). Negative binomial regression models were used to estimate the effect of the UHI on TB mortality rate. Attributable risk (AR) was used as an impact measure. RESULTS: From 2002 to 2015, TB mortality rate decreased by 23.5%, and LC improved. The continuous model analysis resulted in an RR = 0.89 (95%CI = 0.82–0.96), so the AR was -12.3%. The categorized model showed an effect of 0.92 (95%CI = 0.83–0.95) in municipalities with intermediate LC and of 0.83 (95%CI = 0.82–0.91) in those with low LC, representing an AR for TB mortality of -8.7% and -20.5%, respectively. CONCLUSIONS: Improved LC impacted TB mortality, even when adjusted for other determinants. This impact was greater in the strata of low-LC municipalities.